Meta-analysis of the relationship between single nucleotide polymorphism of IL-10-1082G/A and rheumatic heart disease - Dai, Weiran (Oncotarget, 2018)
BACKGROUND: The results showed that there was a certain correlation between the single nucleotide polymorphism of IL-10-1082G/A and rheumatic heart disease, but there was no systematic study to verify this conclusion. AIMS: Systematic review of the association between single nucleotide polymorphism of IL-10-1082G/A locus and rheumatic heart disease. MATERIALS AND METHODS: Computer retrieval PubMed, EMbase, Cochrane Library, CBM, CNKI, VIP and Data WanFang, the retrieval time limit from inception to June 2017. A case control study of single nucleotide polymorphisms and rheumatic heart disease in patients with rheumatic heart disease in the IL-10-1082G/A was collected. Two researchers independently screened the literature, extracted data and evaluated the risk of bias in the study, and using RevMan5.3 software for data analysis. RESULTS: A total of 3 case control studies were included, including 318 patients with rheumatic heart disease and 502 controls. Meta-analysis showed that there was no correlation between IL-10-1082G/A gene polymorphism and rheumatic heart disease [AA+AG VS GG: OR = 0.62, 95% CI (0.28, 1.39), P = 0.25; AA VS AG+GG: OR = 0.73, 95% CI (0.54, 1.00), P = 0.05; AA VS GG: OR = 0.70, 95% CI(0.47, 1.05), P = 0.08; AG VS GG: OR = 0.65, 95% CI (0.22, 1.92), P = 0.43; A VS G: OR = 0.87, 95% CI (0.71, 1.06), P = 0.17]. CONCLUSIONS: When AA is a recessive gene, the single nucleotide polymorphism of IL-10-1082G/A is associated with the presence of rheumatic heart disease. Due to the limitations of the quantity and quality of the included literatures, the further research results were still needed.